Sistemas de informação móveis para o aprendizado colaborativo de libras: uma análise comparativa - SANTOS, Raniely Luz dos (2019)
The present work has as general objective to make the comparative analysis of the performance and functionalities of some mobile applications of translation of the Brazilian Language of Signals and the conception of users about each of the applications used for the test, observing the educational practices developed and the contributions of these in their learning process. For this purpose, a bibliographical research and Field Survey was carried out and as a tool for collecting information we used a questionnaire and personal information from each application, as well as the evaluation of the volunteers. Thus, it was possible to collect information in order to analyze how much mobile applications are useful and efficient with respect to its central objective, which is the translation of LIBRAS. The research made it possible to observe that there is still a great lack of knowledge regarding knowledge about LIBRAS, however, not interfering with learning.